No Association of Folate- Related and Methionine Synthesis Genes Variant in the Development and Progression of Childhood ALL among North Indian Population - Mohsen Nikbakht; Abhimanyu Jha; Kianoosh MalekZadeh; Marjan Askari; Neena Capalash; Marwaha Ram Kumar; Deepak Kaul; Jagdeep Kaur (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Introduction: Acute Lymphoblastic Leukemia (ALL) is the most worldwide common type of childhood cancer. Methylenetetrahydrofolate reductase (MTHFR) and 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR) are crucial enzymes in folate pathways. Folate availability is critical factor for DNA integrity, required for the transfer of methyl group in the biosynthesis of thymidilate. Procedure: In present study, we have conducted a case control study from north Indian states  to correlate the effect of two SNPs of MTHFR (677C→T and 1298A→C) and MTR (2756A→G) and the risk of childhood ALL. One hundred and twenty five bone marrows and peripheral blood samples and 100 sex-age matched healthy controls were obtained and analyzed by PCR-RFLP method. Results: Statistically, no significant differences were observed between patients and controls for different genotypes (p>0.05), also significant different on risk of ALL in individuals having genotype of MTHFR 677TT (OR=0.61, 95% CI=0.21-1.77) and MTHFR 1298CC (OR=0.56, 95% CI=0.18-1.68) was not observed. Statistically, the correlation of variants of MTR gene and risk of ALL was not observed. Conclusions:The difference in distribution of possible combined genotypes of MTHFR (677C→T, 1298A→C) and MTR (2756A→G) between patients and controls were statistically insignificant.